The Impact of Duodenal Diverticuli and the Execution of Endoscopic Retrograde Cholangiopancreaticography. (2nd November 2016) - Loffeld, R. J. L. F.; Dekkers, P. E. P.
Abstract : Introduction. Duodenal diverticuli alter the anatomy of the papillary region and can make an ERCP difficult. Aim. To study the outcome of ERCP in cases of duodenal diverticuli. Patients and Methods. Consecutive ERCPs in a period of 24 years were included. Endoscopy reports were studied for presence of diverticuli. Success of the procedure and findings were noted. Clinical records were searched for clinical presentation of the patient. Patients without duodenal diverticuli were used as comparison. Results. 2795 procedures were done in 2092 patients. Of these, 211 (10%) had diverticuli. Diverticuli occurred significantly more often in women (p < 0.001 ). ERCP was significantly more often inconclusive in cases of a diverticulum, 12.8% versus 6.3%, p < 0.001 . In cases of a successful ERCP, patients with diverticuli showed more often no abnormalities in the bile duct, 26% versus 17%, p < 0.001 . In 64% of cases, the reason for ERCP was cholestasis. There was no significant difference in presence of stones or cholangitis. Biliary pancreatitis was seen more often in patients without diverticuli, 4.4% versus 1.4%, p = 0.04 . This was also the case for malignancies, 18.5% versus 6.6%, p < 0.001 . Conclusion. It is concluded that duodenal diverticuli can be responsible for cholestasis. Presence of a diverticulum in the duodenum makes the ERCP procedure more complex.